Inwestycje zagraniczne w Europie Środkowo-Wschodniej W poszukiwaniu małych barier wejścia - Ząbkowicz, Jerzy (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2005)
The paper is a case study. Using the example of German company: Axel Springer Verlag, the author describes a certain principle which shows that the area of Central and Eastern Europe attracts the attention of small and medium sized companies as well as huge corporations. These companies are changing their strategies and are engaging in a belated „internationalization” of their activity, which has been suffocated in their national markets and has thus led them to search for new areas of domination. Although they are potentially capable of bearing the cost of efficient entry into the mature markets of Western Europe, they prioritize investments in the developing markets. Axel Springer Verlag is a powerful media corporation that has been deeply rooted in the mature and highly stabilized German mass media market for a very long time. Yet instead of using its full potential to radically enhance its position in France or in Spain, the corporation has decided to commence a global conquest of the highly unpredictable markets of former socialist countries.